Lacak Akademik: A Prototyped Early Warning System for Monitoring Student Academic Risk - M Syahid Nur Wahid; Jamaluddin; Muhammad Rais (Information Technology Education Journal, 2025)
The academic condition of students is one of the qualities that must be improved. Various efforts must be made to support the academic improvement. Including the need for monitoring academic conditions to find out conditions early in order to prevent early dropout or dropout of study limits. This research aims to develop the Academic Tracking application as a solution in improving student academic monitoring at the Faculty of Engineering, Makassar State University. This research was conducted through a Research and Development (R&D) approach with a prototype development model. This model allows system design to be done interactively based on user input. The development of this application involves students, academic supervisors, and parents of students, operators, and leaders as the main users. The development process includes the needs analysis stage, design stage, prototyping, user evaluation, system improvement, and final implementation. Testing was conducted using the black box testing method which included six types of scenarios with a total of 34 tests. The test results showed that 33 scenarios were as expected and only one scenario was not, resulting in a score of 95.83%. This application has also been evaluated by several users on various aspects and obtained a score of 88.08% with a very effective status. This application is proven to be effective in monitoring student academic progress more optimally and is expected to reduce student dropout rates. With the features developed, this system can increase the involvement of students, lecturers, and parents in supporting student academic success.